Evaluation of advanced infection and prevention technical training - Ai Siti Sutilah (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2021)
Evaluation of a technical education and training organization can provide positive outputs. This study aims to evaluate the implementation and understanding of the training participants regarding the knowledge of the training materials provided at the Advanced Infection and Prevention Technical Training for Health Workers at the Health Facilities during the COVID-19 Pandemic online, which was held at the Puslatkesda Provinsi DKI Jakarta. This study uses a quantitative description method using the Kirkpatrick Four Levels Evaluation Model, namely through four levels consisting of reaction, learning, behavior, and result. As for what was carried out in the study, it was evaluated at levels 1 and 2. This training was held in October 2020 Batch 1 with 40 participants. Instruments The instrument used is a questionnaire, and the results of the participants' assessment are in the form of pretest and posttestt. The source of data in this study is Puslatkesda data in 2020, namely primary data on the implementation of Advanced PPI Technical Training during the COVID-19 Pandemic. Following are the results of the research data analysis that of the seven evaluation categories at the reaction level to the implementation of the training. The results showed that as many as 18 respondents with a percentage of (45 percent) answered Very Satisfactory, then for reactions to resource persons an average, of 52.5-82.5 percent participants answered satisfactorily and very satisfactory. As for the evaluation of learning or learning, it appears that the average value of participants is 84.3, and there are 100 percent (40) training participants who have complete scores in the posttest stage. With all these descriptions, the Advanced Infection and Prevention Technical Training for Health Workers at Health Facilities during the COVID-19 Pandemic went well and satisfactorily.